2020
DOI: 10.21037/apm.2020.03.28
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of fibroblast growth factor 21 predicts long-term prognosis in patients with both diabetes mellitus and coronary artery calcification

Abstract: FGF-21 among the FGF family members has become a research focus. Different from other FGF members, FGF-21 has no positive effect on the growth of fibroblasts and cannot bind with unfractionated heparin specifically (1).Early studies revealed that the main function of FGF-21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Supplementary Table 1 summarizes the patient selection criteria of these studies. Among these studies, 14 reported serum FGF21 concentration in patients with or without CVDs ( 10 23 ), 14 reported ORs or HRs of serum FGF21 concentration and incidence of CVDs ( 11 , 14 , 17 , 18 , 20 , 24 32 ), 8 reported Pearson's r of serum FGF21 concentration and vascular parameters ( 12 , 15 , 16 , 25 , 30 , 33 35 ), and 6 reported incidence of CVDs in individuals with different serum FGF21 levels ( 27 , 30 , 36 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table 1 summarizes the patient selection criteria of these studies. Among these studies, 14 reported serum FGF21 concentration in patients with or without CVDs ( 10 23 ), 14 reported ORs or HRs of serum FGF21 concentration and incidence of CVDs ( 11 , 14 , 17 , 18 , 20 , 24 32 ), 8 reported Pearson's r of serum FGF21 concentration and vascular parameters ( 12 , 15 , 16 , 25 , 30 , 33 35 ), and 6 reported incidence of CVDs in individuals with different serum FGF21 levels ( 27 , 30 , 36 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…was powered to detect cardiovascular outcomes, and elevated FGF21 levels predicted cardiac death independently of N-terminal pro-BNP levels 24 . More broadly, elevated FGF21 levels have been associated with adverse cardiac events in individuals with coronary disease and/or diabetes, though in subclinical disease such elevations are no longer predictive after adjustment for traditional risk factors 21,22,39,40 . Thus, elevated FGF21 is a potential biomarker for severity in cardiac disease, raising the question of what derangements are causing this elevation, and whether the elevated FGF21 is an intrinsic or hormonal signal for the diseased heart.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, whereas FGF21 appears protective in most animal models of heart disease, elevated levels are poor prognostic indicators in humans. In two studies of diabetic patients with coronary disease, higher levels of FGF21 were predictive of poorer outcomes 21,22 . In cardiomyopathies, FGF21 elevations predicted adverse events in both heart failure with reduced or preserved ejection fraction, though >40% of patients in both these studies had diabetes 23,24 .…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that DM may promote VC by enhancing the expression of inflammatory cytokines, activating bone morphogenetic proteins pathway and receptor activator of nuclear factor-kβ (RANK)/RANK ligand pathway ( 73 ). Recently, Gan et al demonstrated that lower baseline level of FGF21 in serum could predict a better long-term prognosis in patients with both DM and coronary artery calcification ( 22 ). But it has been proved that the application of FGF21 could resist to the calcification of VSMCs by the activation of FGFR1/3/β-klotho/P38/MAPK/runt-related transcription factor 2 signaling pathway ( 72 ).…”
Section: Fgf21 and Diabetic Vascular Complicationsmentioning
confidence: 99%
“…The cardiovascular protective effect of exogenous FGF21 is mainly mediated by the anti-oxidative stress ( 11 ), anti-inflammatory ( 19 ), anti-apoptosis ( 20 ) and lipid-lowering effects ( 21 ). However, despite as a biomarker and diagnostic indicator of DM-related cardiovascular diseases in clinic ( 14 , 22 ), the clinical implementation of FGF21 still has some obstacles due to its complex pharmacokinetic and biophysical characteristics ( 23 ).…”
Section: Introductionmentioning
confidence: 99%